The interlinkage of energy and poverty: evidence from India. (1st September 2004) - Ringel, Marc
Worldwide, some two billion people live without access to modern energy supply. About 1.6 billion people live without access to electricity. Alleviating this "energy poverty" is a factor in reaching most of the UN's millennium goals. In our contribution to the debate on how to achieve this aim, we discuss the nexus between energy and poverty in developing countries. In order to deal with all aspects of energy poverty, the potential to mitigate the lack of energy supply in developing countries is systemised and discussed along the value chain of energy services. It becomes obvious that, at each stage of the chain, the potential to fight energy poverty effectively does exist. The example of India is used in order to highlight the energy-poverty nexus and clarify potentials to overcome the vicious circle of energy-poverty. Finally, we draw conclusions about future needs to tackle the energy-poverty problem.